2021
DOI: 10.1155/2021/5954757
|View full text |Cite
|
Sign up to set email alerts
|

Cilengitide Inhibits Neovascularization in a Rabbit Abdominal Aortic Plaque Model by Impairing the VEGF Signaling

Abstract: Background. Cilengitide is a selective αvβ3 and αvβ5 integrin inhibitor. We sought to investigate the effect of cilengitide on the neovascularization of abdominal aortic plaques in rabbits and explore its underlying antiangiogenic mechanism on human umbilical vein endothelial cells (HUVECs). Materials and Methods. For the in vivo experiment, the abdominal aortic plaque model of rabbits was established and injected with different doses of cilengitide or saline for 14 consecutive days. Conventional ultrasound (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Cilengitide, an arginine-glycine-aspartic acid (RGD) peptide that targets integrins, can selectively inhibit integrin subunit oligomerization, including alpha v, beta3 (α v β 3 ) and beta5 (α v β 5 ) [ 17 , 18 ]. Previous studies have demonstrated that cilengitide inhibited angiogenesis and induced endothelial cell apoptosis via the inhibition of integrins and the extracellular matrix [ 17 , 19 ]. Moreover, cilengitide has also been demonstrated to have antitumor activity by blocking integrin function [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cilengitide, an arginine-glycine-aspartic acid (RGD) peptide that targets integrins, can selectively inhibit integrin subunit oligomerization, including alpha v, beta3 (α v β 3 ) and beta5 (α v β 5 ) [ 17 , 18 ]. Previous studies have demonstrated that cilengitide inhibited angiogenesis and induced endothelial cell apoptosis via the inhibition of integrins and the extracellular matrix [ 17 , 19 ]. Moreover, cilengitide has also been demonstrated to have antitumor activity by blocking integrin function [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In atherosclerosis, activated ERK signaling stimulates the secretion of the proangiogenic factor VEGFA, promoting angiogenic activity in the atheromatous lesion ( 87 89 ). Active angiogenesis within atherosclerotic plaques is harmful, contributing to intraplaque hemorrhage, plaque expansion, destabilization, and rupture ( 90 , 91 ).…”
Section: Erk Signaling In Cardiovascular Diseasementioning
confidence: 99%